Sistem Panduan Identifikasi Kerusakan Mesin DOHC dengan Metode Certainty Factor (Studi Kasus Motor Suzuki Satria fu150) - Alfiyanto, Achmad Rizal; Irawan, Jusak; Sulistiowati, Sulistiowati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2015)
Suzuki Motor Sales (SMS)Undaan is an authorized dealers and workshop center in the area of Surabaya, which sells motorbike with DOHC engine technology that currently becomes most in demand in society. However, the present of these technologies raise new challenge for many mechanics that are less able to cope with the disfunctional engine of the motorbikes. Analysis and design of an expert system might be able to equip the mechanics in handling the DOHC engine failure. Our approach shows that the expert system can identify problems accurately by using the certainty factors method. This application is expected to be able to overcome the mechanics problem in handling the DOHC motorbike engine. And the results obtained from the research that has been done is very helpful for any problems of the motor DOHC engine with 100 % accuracy rate calculations.